1990
DOI: 10.1111/j.1346-8138.1990.tb01643.x
|View full text |Cite
|
Sign up to set email alerts
|

Depletion and Repopulation of Langerhans Cells in Nonsegmental Type Vitiligo

Abstract: The role of Langerhans cells in the pathogenesis of nonsegmental type vitiligo is still unknown. In this study, biopsies were taken from 26 patients at various stages of nonsegmental type vitiligo and morphometrically observed to investigate the kinetics of Langerhans cells in patients at various stages of the disease. A marked depletion of OKT6-positive and ATPase-positive epidermal dendritic cells was noted in patients with active nonsegmental type vitiligo. A repopulation of both OKT6-positive and ATPase-po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0
1

Year Published

1993
1993
2019
2019

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(26 citation statements)
references
References 22 publications
1
24
0
1
Order By: Relevance
“…This cytotoxicity was relatively specific for melanocyte targets [82]. We demonstrated a depletion of epidermal Langerhans cells in patients with active vitiligo, and conversely, a repopulation of these cells in stable vitiligo [55]. These findings support the theory that antibodydependent cellular cytotoxicity is involved in MC destruction in vitiligo.…”
Section: The Immune Hypothesissupporting
confidence: 77%
See 1 more Smart Citation
“…This cytotoxicity was relatively specific for melanocyte targets [82]. We demonstrated a depletion of epidermal Langerhans cells in patients with active vitiligo, and conversely, a repopulation of these cells in stable vitiligo [55]. These findings support the theory that antibodydependent cellular cytotoxicity is involved in MC destruction in vitiligo.…”
Section: The Immune Hypothesissupporting
confidence: 77%
“…We demonstrated that PUVA depletes vitiligo-associated MC antigens and stimulates tyrosinase activity in vitro [56]. Furthermore, PUVA treatment in vivo depletes epidermal Langerhans cells [55]. These may result in (1) blocking the binding of anti-MC autoantibodies to MCs; (2) blocking the progression of antibody-dependent cytotoxicity to MCs in vitiligo; and (3) stimulating melanogenesis.…”
Section: Effects Of Medical Therapies On Repigmentation In Vitiligomentioning
confidence: 96%
“…PUVA and topical corticotherapy are known to induce a depletion in the density of epidermal Langerhans cells. As these treatments induce repigmentation of vitiligo, it was suggested that a therapeutically-induced depletion in stable vitiligo may aid in repigmentation (Kao and Yu, 1990). However, this hypothesis is not supported by another study demonstrating an increase in the number of epidermal Langerhans cells in repigmenting vitiligo (Iyenger et al, 1990).…”
Section: Langerhans Cell Involvementmentioning
confidence: 44%
“…We observed a decreased number of lesional Langerhans cells in seven of ten patients. Four of these patients were receiving UVA radiation therapy and it has been reported that UVA therapy leads to a decreased presence of Langerhans cells in L vitiligo skin (Kao and Yu, 1990;Westerhof et al, 1986). Surprisingly, the tendency toward a more basal location of Langerhans cells seen in PL and L skin was independent of UVA radiation exposure; this is in agreement with the results reported in literature (Birbeck et al, 1961;Westerhof et al, 1986).…”
Section: Immune Infiltrates In Progressive Vitiligomentioning
confidence: 99%